Recent advances in laser gas sensors for applications to safety monitoring in intelligent coal mines - Gong, Weihua; Hu, Jie; Wang, Zhaowei; Wei, Yubin; Li, Yanfang; Zhang, Tingting; Zhang, Qinduan; Liu, Tongyu; Ning, Yanong; Zhang, Wei; Grattan, Kenneth T. V. (Frontiers in Physics, 2022)
Due to the extremely complex working conditions, various health and safety hazards are present in underground coal mines, which cause economic losses and heavy casualties. Among these hazards, methane gas explosion and coal combustion are recognized as the two major hazards to miners. Traditional electronic sensors in mine safety monitoring systems have problems such as low precision, a large amount of maintenance, and monitoring dead zones. In the past decade, gas sensors based on tunable diode laser absorption spectroscopy (TDLAS) have been extensively studied and tailored for use in the coal mine industry, because of the advantages of high sensitivity, high stability, fast response, intrinsic safety, and remote monitoring. This invited paper introduces the recent progress and typical applications of TDLAS-based methane sensors, carbon monoxide sensors, and multi-gas monitoring systems for coal mine gas monitoring, fire prevention, and early warning in intelligent coal mines.